Inhibition of heterocyclic amine formation in beef patties with added spices and ingredients - S. Hinojosa Verdin; K.A. Hachmeister; J. Scott Smith (Kansas Agricultural Experiment Station Research Reports, 2003)
Heterocyclic amines (HCAs) are compounds present at part per billion levels in fried, grilled, broiled, barbecued and smoked meats. Most of these compounds are highly mutagenic, as demonstrated by the Ames test using Salmonella typhimurium. They also are carcinogenic in rodents and non-human primates following high dosage and long term oral administration. For decades, researchers have focused on inhibiting the production of these carcinogens. This research investigates the effects of natural antioxidants in spices or other ingredients on the reduction of heterocyclic amines formation when beef patties are cooked. The term "spice" in this paper includes herbs. Ground beef patties combined with different levels of added spices or ingredients were cooked at 375°F (5 minutes each side) or 400°F (7.5 minutes each side). Extracted HCAs were then analyzed using reversed-phase High Performance Liquid Chromatography (HPLC) with UV-Visible and fluorescence detectors. Of the spices used, basil added at 0.5% was most effective in decreasing HCAs. Of all the ingredients, food starches showed the best inhibition when added at 5% as they reduced MelQx, harman, and norharman forms of HCA at both 375°F and 400°F.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Heterocyclic amine; Spices